Taenia solium and Taenia saginata: Identification of sequence characterized amplified region (SCAR) markers - Dias, Ana Karina Kerche [UNESP]; Aoki, Sérgio Moraes [UNESP]; Garcia, José Fernando [UNESP]; Nunes, Caris Maroni [UNESP] (Elsevier, 2007)
Cysticercosis is one of the most important zoonosis, not only because of the effects on animal health and its economic consequences, but also due to the serious danger it poses to humans. The two main parasites involved in the taeniasis-cysticercosis complex in Brazil are Taenia saginata and Taenia solium. Differentiating between these two parasites is important both for disease control and for epidemiological studies. The purpose of this work was to identify genetic markers that could be used to differentiate these parasites. Out of 120 oligonucleotide decamers tested in random amplified polymorphic DNA (RAPD) assays, 107 were shown to discriminate between the two species of Taenia. Twenty-one DNA fragments that were specific for each species of Taenia were chosen for DNA cloning and sequencing. Seven RAPD markers were converted into sequence characterized amplified region (SCAR) markers with two specific for T. saginata and five specific for T. solium as shown by agarose gel electrophoresis. These markers were developed as potential tools to differentiate T. solium from T. saginata in epidemiological studies. © 2007 Elsevier Inc. All rights reserved.
Keywords: Cestode; deoxyribonucleic acid; DNA; PCR; polymerase chain reaction; random amplified polymorphic DNA; RAPD; SCAR; sequence characterized amplified region; Taenia saginata; Taenia solium; Taeniasis-cysticercosis complex; agarose; DNA fragment; oligonucleotide; controlled study; DNA sequence; gel electrophoresis; genetic marker; molecular cloning; nonhuman; nucleotide sequence; parasite identification; priority journal; Animals; Base Sequence; Cattle; Diagnosis, Differential; DNA, Helminth; Genetic Markers; Molecular Sequence Data; Random Amplified Polymorphic DNA Technique; Species Specificity; Swine; Taeniasis; Animalia; Cestoda; Taenia